Panama : Detailed Assessment Report-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2014)
This report evaluates the level of implementation of Financial Action Task Force (FATF) Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) in Panama. The findings reveal that Panama is vulnerable to money laundering from a number of sources, including drug trafficking and other predicate crimes committed abroad, such as fraud and financial and tax crimes. The AML Law covers most of the core financial sectors but does not fully apply to the insurance sector and does not extend to a number of other financial activities as required under the FATF standard. Competent authorities, including law enforcement and the Financial Intelligence Unit, do not have timely access to information on legal persons and arrangements as required under the FATF standard.